Dribble deficit quantifies dribbling speed independently of sprinting speed and differentiates between age categories in pre-adolescent basketball players - Conte, D.; Scanlan, A. T.; Dalbo, V. J.; Gang, S. Z.; Smith, M. R.; Bietkis, T.; Matulaitis, K. (Biology of Sport, 2020)
The aims of this study were to a) quantify the relationships between sprinting and dribbling speed measured using dribble time and Dribble Deficit and b) assess the difference between age categories in sprinting and dribbling speed in pre-adolescent basketball players. Pre-adolescent, male basketball players (Total, N = 81; Under-10, n = 32, Under-9, n = 49) completed two trials of different tasks including 20-m linear sprints without dribbling, 20-m linear sprints dribbling with dominant and non-dominant hands, and change-of-direction (COD) sprints with and without dribbling. Sprinting time, dribbling time and Dribble Deficit were then calculated for each trial. Spearman rank correlations were used to assess the relationships between outcome measures for Under-9 and Under-10 players separately and combined. The Mann-Whitney U test with effect sizes (ES) was used to assess differences in outcome measures between Under-9 and Under-10 players. Moderate-to-very large significant relationships (p <0.05) between linear and COD sprinting time and dribbling time using dominant and non-dominant hands were found in Under-9, Under-10 and all players combined. Trivial-to-moderate relationships were found between sprinting time and Dribble Deficit in all age categories across linear and COD paths. Quicker performance times (p <0.05) were found for Under-10 compared to Under-9 players in all outcome measures (ES: small-to-moderate), except for COD sprinting time (p >0.05; ES: small). Dribble Deficit measures dribbling speed independently of sprinting speed across linear and COD paths in pre-adolescent basketball players and differentiates between age categories.